Assessing the stakeholders' perception on rice husk ash as supplementary cementitious material using the latent dirichlet allocation model - Go, Sabrina Ashley Ngo (Animo Repository, 2022)
Rice husk ash (RHA) is a byproduct of the rice milling process and is produced through the controlled combustion of the rice husk. Given its high silica content, it is a material that is beneficiary to ordinary Portland cement (OPC). Many studies have been conducted on this material in other parts of the world and is already being implemented, but the researchers have observed that this material is not commonly used in the local construction industry despite the Philippines being a rice-producing nation. The researchers hypothesize that this is due to the lack of research, as stakeholders prioritize more traditional methods over more contemporary ones such as RHA. Given this observation, this study aims to assess stakeholders’ current state of awareness, or perception, of RHA as a supplementary cementitious material (SCM). stakeholders were: the academe, professional organizations, and industry. Documents were collected from these stakeholders using these specific keywords: RHA, sustainability, and geopolymer. The collection was used as input data in the MATLAB program, wherein the researchers used the Latent Dirichlet Allocation (LDA) Model to perform bibliometric analysis on the documents. Based on the results, it showed that the academe has the highest organizational maturity level, generating topic models that mentioned RHA the most frequently. This is followed by the industry at the middle level, and lastly the professional organization at the lowest organizational maturity level, due to their lack of data on RHA. An adoption framework was created based on the organizational maturity and trends observed from the results of the study.